Logistics Governance of the 2024 General Election in Tegal Regency: A Sentiment Analysis of Distribution and Packaging Effectiveness - Aglistya, Ayu Amandha Putri; Zainudin, Arif; Widodo, Agus Setio (Potret Pemikiran, 2025)
The 2024 general election in Tegal Regency involved significant organizational complexity with 1,242,454 registered voters and 4,684 polling stations, necessitating effective logistics governance. Electoral success is determined not only by public participation but also by the effectiveness of logistics governance that ensures the availability of voting equipment in the right time, quantity, quality, and target. This study aims to analyze sentiment regarding the effectiveness of election logistics governance in the 2024 election at the Tegal Regency Election Commission through a multi-stakeholder perspective and identify supporting factors and constraints in the logistics distribution and packaging system. The research employs a qualitative approach with sentiment analysis methodology to examine the effectiveness of election logistics governance. Primary data were collected through in-depth interviews with representatives from four levels of election organizers: Tegal Regency Election Commission (KPU), District Election Committee (PPK), Polling Station Committee (PPS), and Polling Station Working Group (KPPS). Data analysis utilized NVivo 12 Pro software to classify sentiments into positive, negative, and neutral categories. The findings reveal a predominance of negative sentiment encompassing technical constraints in logistics procurement, distribution delays, inadequate supervision, and non-compliance with standard operating procedures. Positive sentiment was identified in distribution timeliness and inter-stakeholder coordination. This research contributes methodologically through the application of sentiment analysis in evaluating election logistics governance and recommends systematic improvements in quality control, human resource training, and time management to enhance the effectiveness of future electoral administration.